Pengaruh Kreativitas Guru dalam Membentuk Keperibadian Peserta Didik di MTs Al Anshori Qomarul Huda Desa Wajegeseng - Abdul Hafiz Alfatoni (PALAPA, 2021)
This study aims to determine whether there is an effect of teacher creativity in shaping the personality of students at MTs Al anshory Qomarul Huda, Wajageseng Village, 2020/2021 academic year. Due to the low personality of students in their daily behavior because of the rampant promiscuity. This is shown when the learning process takes place some students do not pay attention, most students do not do the exercises in the book if they are not ordered by the teacher. Students do not have a good personality to behave in accordance with existing norms. There are even students who do not do assignments even though they have been ordered by the teacher. This research was conducted at Madrasah MTs Al anshory Qomarul Huda, Wajageseng Village with quantitative research type ex post facto design. The population in this study were all students of class VIII totaling 25 people and a sample of 25 people was drawn using saturated samples to test the instrument. Data collection techniques in this study used were documentation, tests and questionnaires. By looking at the average value in the questionnaire is 7.70 and the test has an average value of 7.28. By looking at the coefficient table of the teacher creativity variable = 0.772 so that it is known that the amount of the contribution of teacher creativity to personality is 77.2%, so that it can be concluded by looking at the results of the calculation on the t test, namely the t count on the teacher creativity variable with a significant level of 5% of 0.005 The significance of learning independence is 0.004 and it is obtained that tcount = 3.326 and ttable, 0.05; 24 = 1.176 indicates that 3.326> 1.176. The results showed that there was a positive influence of teacher creativity on the personality of students at MTs Al Anshory Qomarul Huda Desa Wajageseng in the academic year 2020/2021.